Role of Deoxyribonucleoside Kinases and Deoxyribonucleotide Pool Alterations in Nucleoside Reverse Transcriptase Inhibitor Induced Mitochondrial Toxicity - Relucio, K.; Holodniy, M. (Current Medicinal Chemistry - Anti-Infective Agents, 2003)
Adverse events secondary to mitochondrial toxicity is an emerging problem related to treatment of HIV infection with nucleoside reverse transcriptase inhibitors (NRTI). The prevailing hypothesis of mitochondrial toxicity associated with these agents is mitochondrial DNA (mtDNA) depletion as a result of inhibition of the mtDNA polymerase, DNA polymerase γ (DNA Pol γ). However, the inhibition of DNA Pol γ may not be the sole mechanism of mtDNA depletion. Recently, mutations in deoxyribonucleoside kinase (DRNK) genes have been discovered in children with mtDNA depletion syndromes. DRNK are involved in the maintenance of the mitochondrial deoxynucleotide (mtdNTP) pools and in the metabolism of NRTI, and may play a pivotal role in NRTI related mitochondrial toxicity. Studies which focus on the role DRNK in NRTI induced mtDNA depletion and mitochondrial toxicity are needed. It is possible that identifying a mutation or polymorphism in one of the DRNK enzymes could predict differential toxicities between individual and combination NRTI, and could identify which patients are at risk for NRTI-associated mitochondrial toxicity. In addition, elucidating this mechanism could lead to the development of adjunctive drugs or substrates that could ameliorate these toxicities. This review focuses on the following topics: 1) NRTI induced adverse events, 2) Mechanism of NRTI induced mitochondrial toxicity, 3) Summary of clinical and laboratory evidence, 4) Evidence for mechanisms other than DNA Pol g associated mitochondrial toxicity 5) The role of DRNK in mtDNA depletion and relation to activated NRTI induced toxicity, and 6) Considerations for future studies to elucidate the mechanism and to prevent NRTI toxicity.
Keywords: deoxyribonucleoside kinases